Correlation between the particle size of Li1.3Al0.3Ti1.7(PO4)3 solid electrolyte and lithium-ion transport in composite cathodes for all-solid-state lithium-ion batteries - Park, Jae-Ho; Kim, Mingony; Kim, Min-Young; Jeong, Jiwon; Jung, Hun-Gi; Yoon, Woo Young; Chung, Kyung Yoon (Elsevier BV, 2024)
Solid electrolytes (SEs) are key materials for all-solid-state lithium-ion batteries (ASSLBs), and are being studied for various applications. Li1.3Al0.3Ti1.7(PO4)3 (LATP), a NASICON-type SE, is noteworthy due to its wide voltage range for cathode operation and economic feasibility. However, fabricating well-contacted interparticle interfaces in composite cathodes using LATP is challenging because of its high grain-boundary resistance. To address this issue, we investigated the correlation between lithium-ion transport in composite cathodes and the particle size of LATP. We successfully synthesized two LATPs with different size distributions and prepared composite cathodes. Performance evaluation and various advanced analyses of composite cathodes were conducted, the results revealed that LATP with a smaller particle-size distribution formed more a uniform Li+ transfer network in the composite cathode than the larger particles, which contributed to the stable and fast electrochemical characteristics of the ASSLB. Additionally, we also observed real-time structural changes during electrochemical reactions in composite cathodes through in situ X-ray diffraction analysis. The results of our comprehensive analysis are expected to provide valuable insights into the reaction mechanisms of LATP-based ASSLBs, as they have not been extensively explored before.